Studies on the metabolism of SKF 525 A - Barber, Peter John (Rhodes University, Faculty of Pharmacy, Pharmacy, 1978)
Spectrophotometric studies have been carried out to determine the pH dependence of binding of SKF 525 A, Brietal sodium and carbon monoxide to cytochrome P-450. The optimal pH for metabolic conversion of SKF 525 A has been investigated and this agent and its major metabolite, SKF 8742 A, have been metabolised in vitro by swine and rat hepatic microsomes. A suitable gas liquid chromatography assay has been developed and used to analyse metabolic production. The effects of carbon monoxide, dithiothreitol, n-octylamine and of induction of cytochrome P-450 by phenobarbital on metabolism of SKF 525 A and SKF 8742 A have been investigated. Attempts have been made to synthesise SKF 525 AN-oxide.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Drugs -- Metabolism; Cytochrome P-450